Correlation between scientific literacy with higher order thinking skills and self-efficacy in biology learning - May Firdaw Arifiyyati; Ndzani Latifatur Rofi'ah; Listyono Listyono (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
Education is one of the fields or perspectives that have significant developments in the progress of the times. Technological developments are developing the world of education, called the era of the industrial revolution 4.0. Therefore, several things must be mastered, namely competence in each student's life and multiliteracy in mental, physical, and intellectual capacities. One is Science Literacy Ability and Higher Order Thinking Skills (HOTS). In addition to knowledge competence, students must also have confidence in themselves to do and do well, namely self-efficacy. This study aims to determine the relationship between scientific literacy skills, HOTS, and self-efficacy as mediating variables. This type of research is correlational with the survey method. The sampling technique used is Simple Random Sampling with a sample of the population of class XI SMA students who are studying biology. Techniques and data collection instruments using tests in the form of questions (scientific literacy skills and HOTS) and statement questionnaires (self-efficacy). The research was conducted in March-May 2022 at SMAN 3 Semarang. Analysis of research data using quantitative descriptions. The results of this study are that there is a relationship between scientific literacy ability and HOTS with an influence proportion of 7.9%, there is no relationship between scientific literacy ability and self-efficacy with an influence proportion of 0.2%, there is no relationship between HOTS and self-efficacy influence 1.2%.